Evaluation of Pluripotency Gene Expression in Mouse Embryonic Stem Cell Cultured on the Human Feeder Layer - Heidari -Keshel, Saeed; Soleimani, Masoud; khoshzaban, Ahad; Ebrahimi, Maryam; Heidari, Mohammad Hossein (Archives of Advances in Biosciences, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:Arial; p.MsoNoSpacing, li.MsoNoSpacing, div.MsoNoSpacing mso-style-priority:1; mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:Arial; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Embryonic stem (ES) cells are derived from the pluripotent inner cell mass (ICN) cells of blastocysts with the potential to maintain an undifferentiated state indefinitely. The derivation process involves plating of the blastocysts on mouse embryonic fibroblast (MEF) and expansion of the outgrowth in to established ES cell line. ES cell are capable of unlimited self-renewal by symmetric division and differentiated cells to all primitive embryonic germ layers. The capacity of ES cells to differentiate in to almost all the cell types of human body highlights their potential to play a promising role in cell replacement therapies for treatment of human diseases. In this study, MEFs have been replaced with human mesenchymal stem cells (hMSCs). C4 mES cell (mouse embryonic stem cell line) colonies are cultured on inactivated hMSCs amplified ≥ 600-folds during the 30 days of continuous culture. The longest continuous expansion of C4 mES cells on hMSC was 30 passages. In this study the gene expression for Oct-4, Nanog, Rex1, Brachyury, LIF, LIFR, TERT, B2M, Stat3, Sox2, Fgf4 in mES cells using reverse transcriptase polymerase chain reaction (RT-PCR) and in which genes expression for Stat3, Sox2, Fgf4 genes was negative whilst the gene expansion for Oct-4, Nanog, Rex1, Brachyury, LIF, LIFR, TERT, B2M genes was positive. There was also a karyotype analysis for ES which showed normal result. The immunocytochemical analysis of Oct4 transcriptional factor for ES cells was made which showed positive result for this factor. These genes may be novel candidates to play critical roles in the regulation of ES Cell pluripotency and self-renewal.